Managing Between Privacy and Sharing in Group Anti Pelakor Indonesia - Augustin Mustika Chairil; Dwi Masrina (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2023)
Social behavioral change about privacy is phenomenon that we concern in internet user, especially in Anti Pelakor Indonesia (API) Facebook Group. This research studied about women managing private information in social media by observing how members of API Group interpreting of privacy and managing their privacy. This study focuses on the interactivity of members, the meaning of privacy, how manage privacy and what kind of factors make members choose to reveal their privacy in the group. Using a concept of privacy and theoretical approach to Communication Privacy Management (CPM), which is providing assumptions about the system to find out how humans balance decisions about reveal private information. Netnography method used to see virtual activities that occur in groups. The results of the study show that various factors influence the process of privacy disclosure. This research produces a description of how privacy management is carried out by the group members.